Development of Writing Assessment Skills with Psychosocial Involvement for Indonesian Language Teachers - Sukenti, Desi; Agustina; Fauzan, Ahmad; Binti Ramli, Nursabila (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
The assessment of writing skills is very important for improving students' academic performance in the Indonesian language. The phenomenological method is used in this research to investigate the psychosocial involvement of Indonesian language teachers in developing writing skills assessments. Primary data sources consist of interviews with informants, results from field observations, and documents related to the research findings, while secondary data sources consist of written materials relevant to the research results. The data in this study were collected through non-participatory passive observation, interviews, and documentation. The data analysis techniques used are reduction, data display, and conclusion drawing. This research involves twenty Indonesian language teachers to uncover how teachers use writing skill assessments. The results of this study indicate that the development of writing assessment skills for Indonesian language teachers involving psychosocial aspects can mean that Indonesian language teachers need to have a strong understanding that incorporates psychosocial elements. The psychosocial teacher offers a narrative framework to motivate religious values and Islamic behavior that helps individuals articulate their experiences. The assessment of writing skills in Indonesian language learning is influenced by personal moral and spiritual involvement, concepts of life principles, experiences, and literature. These psychosocial principles are given by God to the assessment of writing in the Indonesian language and literature, which is a critical component of the writing assessment development process.